Project-Based Learning Models to Analyze Citizenship Law in Legal Science Subject - Dwi Mustikarini, indriyana; Harmawati, Yuni (Susbtantive Justice International Journal of Law, 2024)
Citizenship law pertains to an individual’s membership within a political society. Acquiring citizenship involves the ability to claim rights and fulfill corresponding obligations. In parallel, the state also possesses rights and obligations toward its citizens. Globalization has significantly impacted the scope of Indonesian citizenship, resulting in certain rights and obligations not being fully accessible to citizens as mandated by the Constitution. The core issue addressed in this study is the analysis of students’ critical thinking skills through the application of project-based learning (PjBL) in the context of citizenship law. Students serve as the primary subjects of this research, as they are the central agents responsible for examining citizenship law, thereby enhancing their critical thinking abilities. The research aims to cultivate critical thinking in the process of designing legislative frameworks and reformulating Indonesian citizenship law. Critical thinking skills are essential for the development of citizenship law, as this legal domain addresses fundamental aspects of human identity and civil rights. Revisions to citizenship law can have widespread implications for individuals, society, and the state. The research employs both qualitative and quantitative descriptive methods. The findings indicate that project-based learning effectively fosters critical thinking in the context of designing and reformulating Indonesian citizenship law.